2013 International Conference on Computing, Electrical and Electronic Engineering (Icceee) 2013
DOI: 10.1109/icceee.2013.6634029
|View full text |Cite
|
Sign up to set email alerts
|

Modeling consumer loan default prediction using ensemble neural networks

Abstract: Abstract-In this paper, a loan default prediction model is constricted using three different training algorithms, to train a supervised two-layer feed-forward network to produce the prediction model. But first, two attribute filtering functions were used, resulting in two data sets with reduced attributes and the original data-set. Back propagation based learning algorithms was used for training the network. The neural networks are trained using real world credit application cases from a German bank datasets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…They also showed that OSS is bad choice for three phase power quality monitoring. Hassan and Abraham [17] showed that OSS was slowest algorithm.…”
Section: One Step Secant (Oss)mentioning
confidence: 99%
“…They also showed that OSS is bad choice for three phase power quality monitoring. Hassan and Abraham [17] showed that OSS was slowest algorithm.…”
Section: One Step Secant (Oss)mentioning
confidence: 99%
“…Peer to peer lending [3], [5], [7], [11], [12], commercial banking [2], [4], [13]- [15], insurance [6], agriculture [16], mortgage [17], and small and medium enterprises (SMEs) [8], [12] are different application areas of loan default prediction studies. However, because of certain specific problems and different available dataset, the studies employed different machine learning models.…”
Section: A) Application Areas and The Problemmentioning
confidence: 99%
“…This, as shown, suggests the type of applicable machine learning model, especially where the size of the available dataset determines the performance. The data features used in building the models reviewed range from eight (8) [2], seventeen (17) [4] to twenty-four (24) [13]. Studies with considerable large datasets are Bagherpour [18] of about 20 million loan observations between 2001 -2006, and Rivet [6] which used 1 million loans data.…”
Section: B) Data Features and The Machine Learning Modelsmentioning
confidence: 99%
See 2 more Smart Citations